SAT1, a glutamine transporter, is preferentially expressed in GABAergic neurons - Solbu, Tom Tallak; Bjørkmo, Mona; Berghuis, Paul; Harkany, Tibor; Chaudhry, Farrukh A. (Frontiers in Neuroanatomy, 2010)
Subsets of GABAergic neurons are able to maintain high frequency discharge patterns, which requires efficient replenishment of the releasable pool of GABA. Although glutamine is considered a preferred precursor of GABA, the identity of transporters involved in glutamine uptake by GABAergic neurons remains elusive. Molecular analyses revealed that SAT1 (Slc38a1) features system A characteristics with a preferential affinity for glutamine, and that SAT1 mRNA expression is associated with GABAergic neurons. By generating specific antibodies against SAT1 we show that this glutamine carrier is particularly enriched in GABAergic neurons. Cellular SAT1 distribution resembles that of GAD67, an essential GABA synthesis enzyme, suggesting that SAT1 can be involved in translocating glutamine into GABAergic neurons to facilitate inhibitory neurotransmitter generation.